2016
DOI: 10.4236/abc.2016.61001
|View full text |Cite
|
Sign up to set email alerts
|

Polyvinyl Alcohol/Polyaniline/ZnO Nanocomposite: Synthesis, Characterization and Bactericidal Property

Abstract: In this study, a new nanocomposite based on Polyvinylalcohol/Polyaniline/Zinc oxide (PVA/PANi/ ZnO) was successfully synthesized. ZnO powder was used to produce its nanoparticles (NPs) using conventional method. PVA/PANi composite was used to produce ZnO NPs. Polyaniline was synthesized in sol solution of PVA in the presence of ammonium persulphate. Morphology and the size of ZnO NPs in nanocomposites were studied via Scanning Electron Microscopy (SEM), X-ray Diffraction (XRD) analysis and Infrared (IR) spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…PVA is a semi-crystalline polymer containing crystalline and amorphous phase 17 which is used in biomedical and pharmaceutical applications 18 and in industries due to the excellent chemical and physical properties, non-toxicity, good chemical resistance, good film formation capacity. 19 It has been applied in production of many end products, as lacquers, resins, surgical threads , and food packaging materials 20 .…”
Section: This Is Anmentioning
confidence: 99%
“…PVA is a semi-crystalline polymer containing crystalline and amorphous phase 17 which is used in biomedical and pharmaceutical applications 18 and in industries due to the excellent chemical and physical properties, non-toxicity, good chemical resistance, good film formation capacity. 19 It has been applied in production of many end products, as lacquers, resins, surgical threads , and food packaging materials 20 .…”
Section: This Is Anmentioning
confidence: 99%
“…successfully synthesized NiO nanostructure by a combustion method which was tested for energy storage and photocatalytic applications. There are numerous reports on the facile synthesis of inorganic NiO nanoparticles 14, 19–24 and synthesis of hybrid polymer nanocomposites such as PVA/NiO, 25 NiO/PVA/SiC, 26 PVA/PANI/ZnO, 27 PMMA‐PVA/TiO 2 , 28 PANI/NiO, 29 PPy/NiO, 30 PANI/CeO 2 , 31 PANI/MnO 2 , 32 PANI/Fe 3 O 4 , 33 rGO/Fe 3 O 4 /PANI, 34 Ag‐PANI DMA‐PSS, 35 Pd/PPy, 36 PPy‐PET, 37 PANI‐Al 2 O 3 , 38 PPY‐PAN‐SiO 2 , 39 and Ag 2 MoO 4 /PPy/GCE 40 using various methods. To date, there are no reports of the preparation of a binary polymer nanocomposite incorporating NiO, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have developed the investigation on the polymeric based ZnO nanocomposites. Samzadeh-Kermani et al reported the synthesis and characterization of PVA-PANI-ZnO ternary nanocomposites prepared via In-situ polymerization method for bactericidal properties [11]. Khan et al studied the synthesis and characterization of the PANI-ZnO nanocomposites.…”
Section: Introductionmentioning
confidence: 99%